2022
DOI: 10.3390/molecules27207136
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Efficacy and Mechanisms of Curcumin-Based Photodynamic Treatment against Staphylococcus aureus and Its Application in Juices

Abstract: Antimicrobial Photodynamic Treatment (aPDT) is a non-thermal sterilization technology, which can inactivate common foodborne pathogens. In the present study, photodynamic inactivation on Staphylococcus aureus (S. aureus) with different concentrations of curcumin and light dose was evaluated and the mechanisms were also investigated. The results showed that curcumin-based aPDT could inactivate S. aureus cells by 6.9 log CFU/mL in phosphate buffered saline (PBS). Moreover, the modified Gompertz model presented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Curcumin has already been used on fruits in various studies, using different carriers to deliver it. It was dissolved directly in juices [41] and incorporated in nanocarriers [42,43] and in films [44,45]. For example, a recent experiment by Chuacharoen [46] showed the effectiveness of curcumin-loaded zein nanoparticles in mango, while Zou [47] designed curcumin-loaded nanoparticles to produce a drink colorant with antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has already been used on fruits in various studies, using different carriers to deliver it. It was dissolved directly in juices [41] and incorporated in nanocarriers [42,43] and in films [44,45]. For example, a recent experiment by Chuacharoen [46] showed the effectiveness of curcumin-loaded zein nanoparticles in mango, while Zou [47] designed curcumin-loaded nanoparticles to produce a drink colorant with antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
“…That could be because the thick layer of peptidoglycan on the outside of Gram-positive bacteria acts as a barrier to releasing intracellular chemicals. Gram-negative bacteria lack such a robust protective barrier, causing E.coli to break down and spill out vast amounts of intracellular protein ( Yuan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…While CUR was less effective in the inhibition of bacterial growth in this study, a decrease in bacterial load was observed in all experimental groups exposed to the biomolecule. Several earlier reports have shown that CUR presents broad-spectrum antibacterial activity and strong biological activity against a variety of bacteria, including potential uropathogens, such as E. faecalis [ 31 ], Acinetobacter baumannii [ 84 ], P. aeruginosa [ 29 ], Klebsiella pneumoniae [ 85 ], S. aureus [ 86 ] and E. coli [ 87 ]. The mechanisms underlying such behavior of CUR are multivariable and often employed simultaneously.…”
Section: Discussionmentioning
confidence: 99%